Marketing Management Analysis of An MSME Restaurant Kebuli Cairo Case Study - Iskandarmouda, Elena Edelweis; Pradini, Gagih; Agustiani, Fitri; Ash-Syifa, Muhammad Azfa; Kusumaningrum, Anisa Putri (CV ODIS, 2023)
Marketing is very important in line with the increasing and increasing needs of the community for quality products making competition tighter in a business environment that continues to grow. With good product marketing, it will be able to increase sales and seize market share. If that has happened then it can be ascertained that the company will 2 get maximum profit. If the marketing of the product is not done or is not appropriate, there will be a decrease in sales which will have an impact on the revenue received by the company. SWOT analysis is the systematic identification of various factors to formulate a company's strategy. This analysis is based on logic that can maximize strengths and opportunities, but simultaneously minimize weaknesses and threats.